Strength and power training did not modify cardiovascular responses to aerobic exercise in elderly subjects - Queiroz,A.C.C. (2011)
Resistance training increases muscle strength in older adults, decreasing the effort necessary for executing physical tasks, and reducing cardiovascular load during exercise. This hypothesis has been confirmed during strength-based activities, but not during aerobic-based activities. This study determined whether different resistance training regimens, strength training (ST, constant movement velocity) or power training (PT, concentric phase performed as fast as possible) can blunt the increase in cardiovascular load during an aerobic stimulus. Older adults (63.9 ± 0.7 years) were randomly allocated to: control (N = 11), ST (N = 13, twice a week, 70-90% 1-RM) and PT (N = 15, twice a week, 30-50% 1-RM) groups. Before and after 16 weeks, oxygen uptake (VO2), systolic blood pressure (SBP), heart rate (HR), and rate pressure product (RPP) were measured during a maximal treadmill test. Resting SBP and RPP were similarly reduced in all groups (combined data = -5.7 ± 1.2 and -5.0 ± 1.7%, respectively, P < 0.05). Maximal SBP, HR and RPP did not change. The increase in measured VO2, HR and RPP for the increment in estimated VO2 (absolute load) decreased similarly in all groups (combined data = -9.1 ± 2.6, -14.1 ± 3.9, -14.2 ± 3.0%, respectively, P < 0.05), while the increments in the cardiovascular variables for the increase in measured VO2 did not change. In elderly subjects, ST and PT did not blunt submaximal or maximal HR, SBP and RPP increases during the maximal exercise test, showing that they did not reduce cardiovascular stress during aerobic tasks.